2020
DOI: 10.2147/rmhp.s268238
|View full text |Cite
|
Sign up to set email alerts
|

<p>Coagulopathy of Patients with COVID-19 is Associated with Infectious and Inflammatory Markers</p>

Abstract: Background: SARS-CoV-2 infection activates coagulation and stimulates innate immune system. Little is known about coagulopathy and response of inflammation and infection in ICU patients with COVID-19. Derangement of coagulation and markers of infection and inflammation induced by SARS-CoV-2 infection, as well as their correlations were elucidated. Methods: One hundred eight ICU patients with COVID-19 (28 survivors and 80 nonsurvivors) in Tongji hospital and Wuhan Jinyintan hospital, in Wuhan, China were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 36 publications
2
28
1
Order By: Relevance
“…Higher CRP levels at admission have been reported in COVID-19 patients with more severe symptoms (24,31). Also, a positive correlation between serum levels of it at admission and chest CT progression has been detected in recent studies (24,(32)(33)(34). Han et al have indicated the optimal cut-off point of CRP at admission is 3.38 mg/L, which may be applicable to predict COVID-19 outcomes (33).…”
Section: Crpmentioning
confidence: 97%
See 1 more Smart Citation
“…Higher CRP levels at admission have been reported in COVID-19 patients with more severe symptoms (24,31). Also, a positive correlation between serum levels of it at admission and chest CT progression has been detected in recent studies (24,(32)(33)(34). Han et al have indicated the optimal cut-off point of CRP at admission is 3.38 mg/L, which may be applicable to predict COVID-19 outcomes (33).…”
Section: Crpmentioning
confidence: 97%
“…Moreover, an increase in serum concentration of this cytokine at days 4 to 6 after the onset of disease symptoms, which decreases over the next few days, is associated with good prognosis (88). It appears a high expression of IFN-g at admission, which continues for 3 to 4 weeks, could cause negative consequences due to over-activity in the immune (30,32,33,37,80), PCT (30,33,38,(51)(52)(53)55), ferritin (33,68) and SAA (73,75,76,78) system, inducing ACE2 expression (the binding site for SARS-CoV-2) and promoting virus replication (87). Anti-IFN-I autoantibodies have recently been detected in COVID-19 and are associated with poor prognosis of the disease.…”
Section: Ifnsmentioning
confidence: 99%
“…Within days after the viral infection, the severely ill patients develop pneumonia that usually progresses to acute respiratory distress syndrome (ARDS), requiring admission to the intensive unit care (ICU) and supplementation with exogenous oxygen [14]. The ICU patients have alterations in blood biomarkers associated with the severity and progression of the disease, such as elevated levels of circulating D-dimer (> 1 µg/mL) [15][16][17], prolonged prothrombin time [18], elevated levels of pro-inflammatory cytokines, and chemokines [15,19], especially IL-6, IL-1β and TNF-α [15,[20][21][22][23], C-reactive protein (CRP), lactate dehydrogenase (LDH), and the activation of the NLRP3 inflammasome [24].…”
Section: Introductionmentioning
confidence: 99%
“…A major part of COVID-19 cases are asymptomatic, although around 20% of patients are severely or critically unwell [13,14]. In those individuals, who present symptoms, common clinical manifestations of COVID-19 include fever, cough, fatigue, sputum production, shortness of breath, sore throat, headache, loss of taste and smell, pneumonia and more advanced cases progress to Acute Respiratory Distress Syndrome (ARDS), coagulation disturbs [15], multiple organ failure, septic shock and death [16]. The patients who progressed to ARDS are evaluate following the Berlin definition [17].…”
Section: Introductionmentioning
confidence: 99%